2020
DOI: 10.1002/aenm.201903294
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hybrid Tandem Solar Cells Based on Optical Reinforcement of Colloidal Quantum Dots with Organic Bulk Heterojunctions

Abstract: While colloidal quantum dot photovoltaic devices (CQDPVs) can achieve a power conversion efficiency (PCE) of ≈12%, their insufficient optical absorption in the near‐infrared (NIR) regime impairs efficient utilization of the full spectrum of visible light. Here, high‐efficiency, solution‐processed, hybrid series, tandem photovoltaic devices are developed featuring CQDs and organic bulk heterojunction (BHJ) photoactive materials for front‐ and back‐cells, respectively. The organic BHJ back‐cell efficiently harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…[9] Several research groups have recently reported various types of CQD-based hybrid tandem solar cells (TSCs). [9][10][11][12][13][14][15][16][17] However, previously reported hybrid TSCs have limitations in improving the PCE. In the case of CQD/CQD-based TSCs, the intrinsic low V OC of CQD limits the PCE.…”
Section: Doi: 101002/adma202004657mentioning
confidence: 99%
See 2 more Smart Citations
“…[9] Several research groups have recently reported various types of CQD-based hybrid tandem solar cells (TSCs). [9][10][11][12][13][14][15][16][17] However, previously reported hybrid TSCs have limitations in improving the PCE. In the case of CQD/CQD-based TSCs, the intrinsic low V OC of CQD limits the PCE.…”
Section: Doi: 101002/adma202004657mentioning
confidence: 99%
“…[15] CQD/organic hybrid TSCs have been proposed as a promising combination since organic solar cells exhibit high V OC and strong absorption. [16] In the conventional device configuration, the organic back cell harvests near-infrared (NIR) light transmitted from the CQD front cell. However, the CQD front cell has a lower bandgap compared to the organic back cell, leading to photocurrent losses in the organic back cell.…”
Section: Doi: 101002/adma202004657mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Aqoma et al reported organic-PbS QD tandem solar cells showing 12% of power conversion efficiency (PCE) recently ( Figure 2b). [31] We organized recent tandem solar cell development in Table 1. [31][32][33][34][35][36][37][38]…”
Section: Tunable Absorption Of Qds By Confined Energy Levelmentioning
confidence: 99%
“…PbS colloidal quantum dot (CQD) solar cells have been rapidly developed in recent years with a certified power conversion efficiency (PCE) up to 13% in an optimal device configuration [ 1 , 2 ]. Compared to traditional photovoltaic technology, PbS CQD solar cells show great potential applications in energy products in view of their low cost, low temperature, and simple solution processing techniques [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. More importantly, the bandgap of PbS CQDs can be easily controlled by varying the size of the CQDs, which enables efficient harvesting of a broad light spectrum from the visible to infrared region.…”
Section: Introductionmentioning
confidence: 99%